РОЗВИТОК ТВОРЧИХ ЗДІБНОСТЕЙ МАЙБУТНЬОГО ВЧИТЕЛЯ У ПРОЦЕСІ НАВЧАННЯ У ВУЗІ (Педагогіка вищої та середньої школи, 2009)
In this article the essence of pedagogical creative works is considered some qualities of creative teacher are defined and the experimental methodic of development of future teachers creative abilities during university training is revealed.